The Study Of Paddy Harvest Losses Determination on Tidal Land in Tanjung Jabung Timur Region Jambi Province. (September 2019) - Nofriati, D; Asni, N; Primilestari, S
Abstract: Good postharvest handling is harvest handling to postharvest activities in accordance with the principles of Good Handling Practices (GHP). GHP implementation is expected to improve the quality of agricultural products and suppress lost harvest. In the paddy commodity, the implementation of GHP covers harvest based on appropriate harvest index, way to harvest, threshing, drying, grinding and storage. The objective of the study was initiated to determine harvest losess and suitability of GHP implementation in reducing losses at harvest and postharvest in the tidal land of Tanjung Jabung Timur Regency. The study was done with observation approach to determine the suitability of postharvest handling innovation based on GHP implementation. To determine of harvest losses by calculate using a formula (SP) = SPS + SSP directly in the field. The results showed that losses at harvest time based on GHP implementation was 1.6% (Inpara 3 varieties), 1.5% (Ciherang varieties) whereas with the way of farmers losses at harvest was higher about 5.1% (Inpara 3) and 4.5% (Ciherang). The results showed that in general situation the farmers were not practicing GHP on harvest and postharvest process.